Lymphopenia predicts disease severity of COVID-19: a descriptive and predictive study (2020)
Dear Editor, An outbreak of an unknown infectious pneumonia has recently occurred in Wuhan, China.1 The pathogen of the disease was quickly identified as a novel coronavirus (SARS-CoV-2, severe acute respiratory syndrome coronavirus 2), and the disease was named coronavirus disease-19 (COVID-19).2 The virus has so far caused 78,959 confirmed cases and 2791 deaths in China according to the reports of government. COVID-19 has been spreading in many countries such as Japan, Korea, Singapore, Iran, and Italia. The clinical manifestation of COVID-19 include fever, cough, fatigue, muscle pain, diarrhea, and pneumonia, which can develop to acute respiratory distress syndrome, metabolic acidosis, septic shock, coagulation dysfunction, and organ failure such as liver, kidney, and heart failure.1,3,4 Unfortunately, there is no effective medication other than comprehensive support. However, the mild type of COVID-19 patients can recover shortly after appropriate clinical intervention. The moderate type patients, especially the elderly or the ones with comorbidity, can worsen and became severe, indicating high mortality rate.3,4 However, efficient indicators for the disease severity, therapeutic response and disease outcome have not been fully investigated. Once such indicators are present, reasonable medication and care can be inclined, which is believed to significantly reduce the mortality rate of severe patients.